VALUABLE ASPECTS OF THE AESTHETIC CULTURE OF INDIVIDUALS AND SOCIETY IN A FREE CIVIL SOCIETY (Eureka Journal of Humanities and Social Research, 2026)
During the years of independence, in the process of building a free civil society, the aim of democratic reforms was to ensure the attainment of a high spiritual culture by every individual, to raise and develop a healthy generation, to form a comprehensively and harmoniously developed person, and to nurture a morally upright and aesthetically pure and mature individual. For this purpose, the Development Strategy of New Uzbekistan for 2022-2026 has been developed in our multinational country. This strategy identifies the following as key priorities for our development: improving state and societal structures, ensuring the rule of law and reforming the judicial and legal system, further developing and liberalizing the economy, advancing the social sphere, ensuring security, fostering interethnic harmony and religious tolerance, and pursuing a well-considered, mutually beneficial, and pragmatic foreign policy [1].